Cassava growers' association - Nigeria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A Cassava Growers'Association has been formed in Nigeria with the aim of getting greater numbers of farmers to adopt new technology for this important food crop. The main aims of the Association are to: - acquaint cassava farmers with the potential...